Política antitruste: aspectos relevantes para o caso brasileiro - Monteiro, Carmen Diva Beltrão (2003)
This work intends to show some aspects of antitrust policy that are relevant to the Brazilian case. For this purpose, it has five parts. Chapter I - Introduction, as the title suggests, simultaneously introduces and emphasizes what will be shown in the next chapters. Chapter II - General view or understanding the antitrust gives a comprehensive view of the historical evolution on antitrust matters, explores the relationship between State action, globalization and competitiveness and presents some of the essential concepts on antitrust field. Chapter III - The antitrust policy in Brazil focuses on the legal evolution of antitrust institutes in Brazil - highlighting its strategic dimension and insertion on 'Plano Plurianual - PPA', the Brazilian official long-run plan - and presents the 'Sistema Brasileiro de Defesa da Concorrência - SBDC', the Brazilian system for defence of competition. Chapter IV - Antitrust policy, connections and consequences shows the relevant links and inferences to the Brazilian case such as the development of competitive advantages, the formulation of competitive strategies, the well-known objectives and instruments of antitrust policy, the acceptable principles to an antitrust institutional design and, finally, the critical aspects of the Brazilian current model together with the suggestions to improve it. To finish, Chapter V - Final considerations outlines some reflections regarding the previous exposed antitrust matters.